Tannins Compound In Soga Tingi Bark (Ceriops Tagal) As Natural Dyes - Paryanto, Paryanto; Pranolo, Sunu Herwi; Susanti, Ari Diana; Putrikatama, Bintang Timur; Qatrunada, I. R.; Wibowo, Angga Dwi (Program studi Teknik Kimia UNS, 2021)
In general, natural dyes for textile materials are obtained from extracts part of the plants such as roots, wood, leaves, seeds, and flower. Textile industry especially batik craftsman, have known many plants that can dye textile materials, such as indigo (indigofera), soga tingi bark (Ceriops tagal), tegeran wood (Cudraina javanensis), turmeric (Curcuma), tea (The), noni root (Morinda citrifelia), soga jambal bark (Pelthophorum ferruginum), kesumba (Bixa orelana), and guava leaf (Psidiumguajava). Soga tingi bark chosen because it can produce tannins which can be used as natural dyes. The purpose of this research was to obtained tannin content in soga tingi bark as qualitatively and quantitatively. The analysis carried out is FTIR and HPLC method. FTIR analysis carried out to determine of the compounds contained in the soga tingi bark extraction. Based on FTIR analysis it can be seen that there are O-H and N-H group in the wavenumber 3375,13 cm-1. C=O bond at wavenumber 1739,16 cm-1. C=C bond at wavenumber 1624,31 cm-1. C-H bond at wavenumbers 2970,72 cm-1, 1456,39 cm-1, and 1365,74 cm-1. NO2 bond at wavenumber 1365,74 cm-1. C-N bond at wavenumbers 1228,69 cm-1 and 1217,34 cm-1. And C-O bond at wavenumbers 1228,69 cm-1, 1217,34 cm-1, and 1052,3 cm-1. While HPLC analysis carried out to determine contains tannin level in the soga tingi bark extraction. HPLC conditions used are Flowrate: 1 mL/min, Mobile phase: MeOH : H2O (50:50), λ: 271 nm and Column: C18, 250 mm. Based on HPLC analysis it is known that the contains tannin level in the soga tingi bark extraction is 22,44 ppm.